Improving Early Reading Ability Using Animated Videos in Dyslexic Students (Single Research Subject in Grade IV of SD Negeri 22 Koto Lalang, Padang City) - Mexxy Novia Sartika; Damri Damri (Edumaspul: Jurnal Pendidikan, 2022)
This study discusses improving early reading skills using animated videos in dyslexic students in fourth grade at SD Negeri 22 Koto Lalang. This research was motivated by a problem that the researchers found when conducting observations in the fourth grade of SD Negeri 22 Koto Lalang, Padang City who had difficulty learning to read (dyslexia). Students have difficulty in beginning reading, especially in reading nouns that use the letter E and letter F. The purpose of this study was to prove that the use of animated video media can improve early reading skills in dyslexic students in grade IV SD Negeri 22 Koto Lalang in the city of Padang. This research uses quantitative research methods with experimental research types and uses a single subject research form with an A - B - A design. The research subject used is a dyslexic student in class IV SD Negeri 22 Koto Lalang, Padang City. The data collection technique used is an action test. The data were analyzed using graphic visual analysis. The results of the research that have been carried out show that the initial reading ability increases after being given an intervention using animated video media.